ANALISIS DESKRIPTIF KETERAMPILAN MENGINTEGRASIKAN AL-QUR’AN DALAM PEMBELAJARAN PADA MAHASISWA PGMI - Hanifah, Desty Putri (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
The objective of this study is to examine the abilities of students enrolled in the PGMI program with regard to integrating the Qur'an into their learning process. A descriptive qualitative approach was employed in the study, which was conducted on 30 fifth-semester PGMI students at the University of Science Al-Qur'an Wonosobo. The students were selected through purposive sampling. Data were collected through participant observation, in-depth interviews, document analysis, and open-ended questionnaires. The findings of the study indicated that students exhibited varying degrees of conceptual understanding, with 45% demonstrating a basic comprehension, 35% displaying a methodological understanding, and 20% exhibiting a comprehensive familiarity with the subject matter. In the implementation of integrated learning, three integration patterns were identified: direct (55%), analogical (30%), and reflective (15%). The primary challenges encountered pertain to conceptual aspects (interpretation and identification of verses), methodological aspects (learning models and media development), and practical aspects (time management and learning evaluation). In light of these findings, it is recommended that a gradual development model be implemented, comprising three phases: foundation reinforcement, guided practice, and independent development. The findings of this study indicate a need for a reconstruction of the PGMI curriculum that places greater emphasis on the systematic and sustainable development of integration competencies.